HISTORY OF SURGERY TEMPOROMANDIBULAR JOIN - P. G. Sysolyatin; S. P. Sysolyatin; O. D. Baydik; O. V. Il’enok (Бюллетень сибирской медицины, 2016)
The article presents the main stages of the historical development of the temporo-mandibular joint surgery. It was shown the evolution of treatments for diseases and injuries of joints. It summarizes the main work of domestic and foreign authors that influenced the development of surgery of the temporo-mandibular joint.